Long-term biosolids use in agricultural lands : effects on selected soil chemical properties, accumulation of triclosan and sulfamethoxazole in the soil and maize plant - Tesfamariam, Eyob Habte (University of Pretoria, 2022)
Dissertation (MSc Agric (Soil Science))--University of Pretoria, 2021.